Identifying the role of cocking phase during jump throwing in handball using 3d kinematic analyses - Akl, A.; Hassan, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: In handball throwing, acceleration phase is very important and the most researchers focused on it. Although, it depends on the cocking phase, there is a lack of research that regarding to determine the role of cocking phase during jump throwing in handball. Therefore, this study aimed to determine the role of cocking phase using 3D kinematic analyses. Methods: Ten Handball players participated in this study (age: 20.8 ± 1.21 years; body mass: 82.8 ± 8.57 kg; height: 189.6 ± 8.65 cm). After 15-minute warm-up, the participants completed jump-throws from the 7-m penalty line after three running steps. A total of five successful attempts were recorded for each participant, one minute rest between attempts. The best attempt was selected for 3D analyses. Eight synchronised high-speed cameras were used at a 100 Hz frequency. SIMI 3D motion analyses system was used for capture and analyses. The 3D coordinates were the X (medio-lateral), Y (anterior-posterior) and Z (vertical) directions respectively. Results: There are significant correlations between ball velocity with linear and angular kinematics (displacement, velocity, acceleration) at cocking phase more than acceleration and following phases, displacement of COM Y (r=0.710, p<0.05), velocity of COM Y (r=0.838, p<0.01), shoulder velocity (r=0.686, p<0.05), velocity of COM Y at acceleration phase (r=0.892, p<0.01). Discussion: Results emphasised the role of cocking phase, according the strong correlation significant between displacement and velocity in the anterior-posterior dimension (movement direction) with ball velocity. Furthermore, the relationship of cocking displacement and velocity indicated to these contributions to increase both of displacement and velocity in the acceleration phase to gain maximum work and power. In addition, shoulder velocity is one of the important parameters that associated with the increase of ball release (Wagner et. al., 2011).